Post COVID-19 Symptoms Among Infected Vaccinated Individuals: A Cross-Sectional Study in Saudi Arabia - Heba M. Adly; Saleh A. K. Saleh; Mohammed A. Garout; Altaf A. Abdulkhaliq; Abdullah A. Khafagy; Abdullah A. Saati; Imad A. AlJahdali; Maher N. Alandiyjany; Jaffar A. Al-Tawfiq (Springer, 2023)
Abstract Introduction Multiple studies investigated the endurance and occurrence of symptoms three months after SARS-CoV-2 infection. This study examines the possible effects of COVID-19 vaccination on the persistence of post-recovery symptoms. Patients and Methods A cross-sectional survey was conducted in Saudi Arabia to evaluate 14 prevalent long COVID-19 symptoms among vaccinated individuals. Patients self-reported their acute COVID-19 experience, demographic information, chronic conditions, vaccine history, and persistent symptoms. Results Of the 484 patients, four respondents were excluded from the study as they had not received the vaccine, and 111 (23.1%) were vaccinated but did not get infected and were also excluded. The remaining 369 (76.9%) reported COVID-19 and a vaccination and thus they were included in the study. The occurrence of post-COVID-19 symptoms was reported in 59 (16.1%) for ≤ 3 months, 202 (54.8%) experienced persistent symptoms 3-6 months, and 108 (29.1%) reported symptoms lasting > 6 months. In relation to age group, persistent symptoms 3-6 months after recovery was more common in those > 50 years and symptoms lasting > 6 months were more common in 30-50 years of age (p < 0.001). Persistence of symptoms for  3-6 months was more common in those who were infected prior to vaccination compared to those who were infected after vaccination (P < 0.001). Of the included patients, 323 (87.5%) rated their health as good, 41 (11.1%) considered it fair, and 5 (1.4%) described their well-being as poor or terrible. Conclusion The study provides information of persistent symptoms in vaccinated individuals who had recovered from COVID-19 and highlights the need for targeted interventions to alleviate post-COVID-19 symptoms. The study is limited by its reliance on self-reported data and potential selection bias. Future research is needed to understand the mechanisms underlying persistent symptoms in vaccinated individuals and to identify effective interventions for long COVID.